Urban Land Use and Environmental Health Risks: Assessing Human Exposure to Microplastic Pollution in The River Benue Watershed, Makurdi, Nigeria - Odediran Bukola Sunday (RADINKA JOURNAL OF HEALTH SCIENCE, 2026)
Rapid urban expansion and unregulated land use change in sub-Saharan African cities intensify the discharge of microplastic contaminants into inland freshwater bodies, leading to human health risks. The River Benue watershed in Makurdi, Nigeria is under mounting pressure from agricultural runoff, industrial effluents and inadequate solid-waste management, yet baseline data on microplastic contamination and associated health risk remain scarce. This study quantifies and characterises microplastic concentrations in surface water and sediments of the River Benue across sites stratified by dominant land use. Water and sediment samples were collected in triplicate from six sites representing urban commercial, peri-urban agricultural and residential land use zones along a 14 km transect of the river during dry and wet seasons (January–June 2024). Microplastics were isolated via density separation and vacuum filtration, characterised morphologically under stereo microscopy, and polymer-typed by micro-Fourier Transform Infrared Spectroscopy (μ-FTIR). Estimated Daily Intake (EDI), Hazard Quotient (HQ), and Monte Carlo simulation were applied for health risk modelling. Microplastic concentrations ranged from 120 ± 18 to 406 ± 43 particles/L in surface water and from 284 ± 31 to 1,142 ± 98 particles/kg dry weight in sediment. Fibres (54.7%) and fragments (26.3%) dominated morphologically; polyethylene terephthalate (PET, 31.2%), polypropylene (PP, 22.8%), and polyethylene (PE, 19.5%) were the most abundant polymers. Concentrations were higher at commercial sites and correlated positively with population density and distance from formal waste disposal infrastructure. The mean EDI for adults via water ingestion was 1.87 × 10⁻² mg/kg-bw/day. Monte Carlo-derived HQ values ranged from 0.83 to 2.14, indicating sub-populations near high-load sites may face non-trivial health risk. Urban land use intensity is a primary determinant of microplastic loading in the River Benue, with health risk estimates exceeding safety thresholds for vulnerable sub-populations. Targeted land use regulation, improved solid-waste infrastructure, and systematic riverine monitoring are urgently needed in Makurdi and comparable Nigerian cities